Traditional use Antifungal, Antibacterial of local Iraqi Medicinal Plants: in Review (Eurasian Journal of Research, Development and Innovation, 2024)
The Present review was conducted to explain the role of Iraqi medicinal plants in traditional medicine. This review is an attempt to highlight the traditional uses of Iraqi medicinal plants. Plants produce chemical compounds as part of their normal metabolic activities. Plants are a valuable source of a wide range of secondary metabolites, which are used as pharmaceuticals, agrochemicals, flavours, fragrances, colours, biopesticides and food additives